O-001 Thrombectomy for acute ischemic stroke patients aged 80 years or older: long-term outcomes in 233 patients. (12th July 2011) - Nogueira, R; Smith, W; Jovin, T; Liebeskind, D; Budzik, R; Walker, G; Baxter, B; Rymer, M
Abstract : Background: Advanced age has been identified as one of the strongest predictors of poor outcomes after acute ischemic stroke (AIS). In fact, it remains unclear whether AIS patients aged 80 years or older benefit from revascularization therapies. The purpose of this study is to describe the clinical outcomes after thrombectomy in a large cohort of elderly patients. Methods: All data from two prospective clinical trials (MERCI, n=141; Multi MERCI, n=164) and one prospective registry (n=1000) involving thrombectomy with the MERCI device for the treatment of AIS due to intracranial arterial occlusions was combined in a dataset totaling 1305 patients. The entry criteria for the current analysis included: Age ≥80 years; Baseline mRS ≤1, and available functional outcomes at 90 days. Descriptive analyzes of baseline clinical and angiographic characteristics as well as the rates of symptomatic ICH were obtained. The rates of good functional outcomes (mRS ≤2) and mortality at 90 days was calculated for the overall group as well as for revascularized (TIMI/TICI 2-3) and non-revascularized (TIMI/TICI 0-1) patients. Uni- and multivariate lognistic regression analyzes was performed to identify the predictors of good clinical outcome and mortality in this patient population. Results: A total of 233 patients met the criteria for the study. The median age was 84.2 years (mean, 84.8; range 80–96). 65% of the patients were females. The mean baseline NIHSS was 18.88±6.29 (median, 18). Time from symptom onset to arterial puncture was 5.06±2.95 h (median, 4.42). 57% of the patients were intubated. Pre-procedural IV rt-PA was given to 24.5% and 47.6% of the patients received adjuvant IA lytics. Occlusion site included the ICA in 32.6%, MCA-M1 in 53.6%, MCA-M2 in 9.4%, and vertebrobasilar in 4.3% of the patients. The overall recanalization rate (TICI 2a/2b/3 or TIMI 2/3) was 73.4% and 17.3% of the patients achieved a mRS ≤2 at 90 days. The 90-day mortality was 55.2%. Post-Procedure TICI 2b/3 or TIMI 2/3 was the only independent predictor of good outcome (OR 6.93, 95% CI [2.86 to 16.78], p<0.0001). Higher baseline NIHSS score (OR 0.94, 95% CI [0.89 to 1.00], p=0.0576) and baseline Modified Rankin score (1 vs 0) showed a significant trend toward lower chances of good outcome. Post-Procedure TICI 2b/3 or TIMI 2, 3 (OR 0.22, 95% CI [0.11 to 0.43], p<0.0001), CHF (OR 3.35, 95% CI [1.49 to 7.58], p=0.0036), ICA occlusion (OR 2.55, 95% CI [1.23 to 5.28], p=0.0116), Baseline Modified Rankin Score (OR 3.43, [1.30 to 9.04], p=0.0127), Baseline Diastolic Blood Pressure (OR 1.03 95% CI [1.01 to 1.05], p=0.0135), Time from Symptom Onset to Arterial Puncture(hrs) (OR 0.87 95% CI [0.77 to 0.98], p=0.0239), and INR>1.7 (OR 0.27 95% CI [0.08 to 0.95], p=0.0405) were independent predictors of 90-day mortality. At 90 days, the rates of good functional outcomes were significantly higher (22.9% vs 1.6% %, p<0.0001) and mortality was lower (47.4% vs 77.0%, p<0.0001) in successfully revascularized as compared to non-revascularized patients. Conclusion: Despite an overall lower chance of independent outcomes, successful revascularization is strongly associated with improved outcomes in elderly AIS patients treated with thrombectomy. Our data suggest that the decision to provide endovascular therapy should not be solely based on patient's age.